The implementation of Malay archipelago elements towards 2D animation production of Hang Nadim folktales - Nor Ashikin, Sabran (Universiti Malaysia Sarawak (UNIMAS), 2013)
This research holds to implement Malay Archipelago local identity elements into Malaysia's 2D animation. Experimentation has been conducted emphasized on the character design, bacground props and storytelling. The integration of creative local contents has been given strictly intention in 2 D animation pre-production, production and post-production phase of hang Nadim's folktales